Embodied Value: Egg Donation, Visuality and Cyberculture in the United States - Boulay, Kate (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
This article examines selected examples of the contemporary American fertility industry's commercialized cyberculture. Foregrounding one clinic's egg donor recruitment campaign, and drawing on interviews conducted with industry practitioners, it tracks the ways in which efforts to sell assisted conception online depend upon a visual economy of whiteness.